Refeeding Syndrome - Dhungel, Samriddh; Ghimire, Prabina; Thapaliya, Rasmila; Acharya, Nishant; Pokhrel, Anil (Journal of Nepal Health Research Council, 2019)
Refeeding syndrome is a potentially fatal alteration in serum electrolytes occurring in patients refed after a period of starvation. Its actual incidence is not established due to lack of universally acceptable definitions. 88 years lady presented with negligible food intake for 15 days,mild dehydration and a BMI of 16.8kg/m2. Rigorous refeeding was started and patient developed hypophosphatemia, hypomagnesemia and ventricular premature contractions. Patient was diagnosed with refeeding syndrome and treatment was started. She recovered uneventfully and was discharged with nasogastric tube in situ on day 10 of admission. Refeeding syndrome is commonly encountered but mostly overlooked diagnosis and is a significant cause of nutritional morbidity and mortality in patients with chronic malnourishment.Keywords: Hypophosphatemia; refeeding; refeeding syndrome.